Human Trafficking Around the World - STEPHANIE HEPBURN, RITA J. SIMON (Columbia University Press, 2013)
We have all seen fi lms that portray the dark and lurid world of human traffi cking, depictions that seem sensationalized and exaggerated for cinematic effect. The victims are usually young women forced into an underground sex-traffi cking ring, kept on a permanent drug high, and forced to prostitute. Although the plot is horrifying, it is just a story to us— or perhaps it is something that happens in some other part of the world but surely would never occur where we live. Yet the reality is that wherever we may live, regardless of city or nation, some form of human traffi cking exists. As of 2005 this global phenomenon reaped an annual worldwide profi t of $44.3 billion and affected more than 12.3 million persons. The International Labour Or ga ni za tion (ILO) estimated that 43 percent of victims were traffi cked for commercial sexual exploitation, 32 percent were traffi cked for forced labor, and the remaining 25 percent were traffi cked for a mixture of both or for undetermined reasons (Belser, 2005, p. 4; ILO, 2006). We believed the percentage of forced labor to be higher, and recent ILO global estimates concur. The International Labour Or ga ni za tion now estimates that 20.9 million are victims of forced labor. Within that number it is estimated that 14.2 million people (68 percent) are victims of forced labor exploitation and 4.5 million (22 percent) are victims of forced sexual exploitation. The remainder of victims— 2.2 million (10 percent)— are in state- imposed forms of forced labor such as that imposed by rebel armed forces, state militaries, and prisons with conditions that confl ict with ILO standards (ILO, 2012, p. 13)